2021
DOI: 10.4314/ahs.v21i1.35
|View full text |Cite
|
Sign up to set email alerts
|

Neurological manifestations following cured malaria: don’t forget post-malaria neurological syndrome

Abstract: Introduction: Cerebral malaria which occurs during the active infection is the most common neurological complication of malaria. Other complications including post-malaria neurological syndrome (PMNS) can rarely occur following complete recovery from the disease. We report a case of post-malaria neurological syndrome in a Tunisian patient. Case presentation: A 26-year-old Tunisian man with no past medical history was admitted in 2016 for a muscle weakness of the 4 limbs, seizures, tetraparesis and myoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The use of MRI in malaria research studies is relatively new and was limited to single case studies for a long time ( Bellazreg et al., 2021 ; Schubert et al., 2021 ), before gradually becoming more available in endemic areas. A study of 24 adults demonstrated that brain swelling and increased volume is common in CM due to iRBC sequestration in the brain ( Looareesuwan et al., 1995 ).…”
Section: Diagnosis Neuroimaging and Limitations Of Diagnosismentioning
confidence: 99%
“…The use of MRI in malaria research studies is relatively new and was limited to single case studies for a long time ( Bellazreg et al., 2021 ; Schubert et al., 2021 ), before gradually becoming more available in endemic areas. A study of 24 adults demonstrated that brain swelling and increased volume is common in CM due to iRBC sequestration in the brain ( Looareesuwan et al., 1995 ).…”
Section: Diagnosis Neuroimaging and Limitations Of Diagnosismentioning
confidence: 99%
“…One such was a case series that involved 10 patients in Thailand [ 34 ]. In a case report from Tunisia, the patient presented with tetraparesis [ 36 ]. Bilateral facial nerve palsy which is considered a feature of AIDP has been reported in India [ 37 ] and in South Korean [ 38 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Brain CT scan was normal in some cases including [ 36 , 42 , 43 , 49 – 51 ]. In some other cases the CT scan was abnormal.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…31 HPV/HIV confection in Kenya 32 , and first line HIV treatment failure in Ethiopia 33 , conclude the HIV papers. We have a series of papers on malaria 34 , septic shock 35 , and wound infection with MRSA 36 concluding the infections disease section.…”
Section: Infectionsmentioning
confidence: 99%